2017
DOI: 10.1002/bse.1969
|View full text |Cite
|
Sign up to set email alerts
|

Setting Strategies outside a Typical Environmental Perspective Using ISO 14001 Certification

Abstract: The scope of this research is to evaluate whether ISO 14001 certification could be used as a strategic vehicle for achieving objectives that are not strictly linked to a technical and operative perspective, and to determine what these objectives are. In order to find these objectives, a review of the literature was first conducted to determine what they were and seven hypotheses emerged. The hypotheses concerned the possibility of using ISO 14001 as a strategy for achieving objectives related to finance and tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 48 publications
0
35
0
1
Order By: Relevance
“…In addition, firms can improve environmental management and performance after being certified (Zobel, 2013). Empirical studies have shown a positive connection between certification and positive environmental outcomes (Chiarini, 2017;King et al, 2005;Qi et al, 2013), which means that certification might convey information about environmental improvement to external stakeholders, such as suppliers and regulators.…”
Section: The Signaling Effect Of International Certificationmentioning
confidence: 99%
“…In addition, firms can improve environmental management and performance after being certified (Zobel, 2013). Empirical studies have shown a positive connection between certification and positive environmental outcomes (Chiarini, 2017;King et al, 2005;Qi et al, 2013), which means that certification might convey information about environmental improvement to external stakeholders, such as suppliers and regulators.…”
Section: The Signaling Effect Of International Certificationmentioning
confidence: 99%
“…In the last two decades, the dissemination of voluntary environmental certifiable reference standards to implement environmental management systems (EMSs) has gained momentum. These standards specify sets of internal organizational environmental practices and a system for third‐party audits to certify the commitment to the standard's requirements, but no performance levels (Boiral, ; Chiarini, ; Delmas, ; Iatridis & Kesidou, ; King, Lenox, & Terlaak, ). The ISO 14001 voluntary environmental certifiable standard is the main reference model (Boiral, Heras‐Saizarbitoria, & Testa, ; Daddi, Testa, Frey, & Iraldo, ) and has been adopted by more than 360,000 organizations worldwide (ISO, ).…”
Section: Introductionmentioning
confidence: 99%
“…Voluntary certifiable standards for corporate environmental management formalize, systematize, and legitimize a very diverse set of managerial activities and are being adopted by an increasing number of organizations across the world (Boiral, Guillaumie, Heras‐Saizarbitoria, & Tayo Tene, ; Boiral, Heras‐Saizarbitoria, & Testa, ; Demirel, Iatridis, & Kesidou, ; Iatridis & Kesidou, ), despite a certain level of saturation and decline in the dissemination of these standards has been also evidenced (e.g., Chiarini, ; Daddi, De Giacomo, Frey, & Iraldo, ). Among these standards, the environmental certifiable management system standards, also referred to as meta‐standards, are the most prominent (Baek, ; Chiarini, ; Heras‐Saizarbitoria & Boiral, ; Qi, Zeng, Li, & Tam, ). These certifiable standards, such as ISO 14001 and the Eco‐Management and Audit Scheme (EMAS), are based on traditional principles of management, such as the plan–do–check–act (PDCA) cycle of continual improvement, and have similar external certification processes.…”
Section: Introductionmentioning
confidence: 99%